DSP-based PLL-controlled 50-100 kHz 20 kW high-frequency induction heating system for surface hardening and welding applications - Bayindir, NS; Kükrer, O; Yakup, M (Iee-Inst Elec Eng, 2003)
A digital signal processor (DSP)-based phaselocked loop (PLL)-controlled high-frequency induction heating system is described. The rectifier and insulated gate bipolar transistor (IGBT) inverter are controlled by a TMS320F240 DSP system, which has the hardware feature of providing a dead-band delay independent of the frequency of operation. This feature, together with the high speed of the DSP, allows the use of zero current resonant switching at a high power factor for frequencies up to 100 kHz. Resonant operation of the inverter is maintained by a simple digital PLL scheme implemented on the DSP. The frequency converter enables safe operation at all load conditions with digital overcurrent, overvoltage and overtemperature protection features. The cost-effective system described is operated successfully at outputs up to 19.8 kW at 72 kHz and 500 V.
Keywords: Inverter